2017
DOI: 10.1513/annalsats.201606-463oc
|View full text |Cite
|
Sign up to set email alerts
|

Sinus Computed Tomographic Findings in Adult Smokers and Nonsmokers with Asthma. Analysis of Clinical Indices and Biomarkers

Abstract: We found an association between the severity of sinusitis on CT imaging and the severity of concomitant asthma on spirometry for nonsmoking adults but not for smokers. In adults with asthma, CT imaging evidence of severe sinusitis indicates intense Th2-related inflammation, regardless of smoking status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 36 publications
0
47
2
Order By: Relevance
“…The details of the materials and methods used in this study were described in our previous report and can be found in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The details of the materials and methods used in this study were described in our previous report and can be found in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…The Hokkaido Severe Asthma Cohort Study (the Hokkaido‐based Investigative Cohort Analysis for Refractory Asthma [Hi‐CARAT]) is a multicenter observational cohort study, which primarily aims to characterize subjects with severe asthma, including those who smoke. The details of this study protocol have been reported previously . Patients with severe asthma were enrolled at Hokkaido University Hospital and its 29 affiliated hospitals and clinics between February 2010 and September 2012.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Details of the pulmonary function tests are described in the online supplement and in our previous report [6, 7]. …”
Section: Methodsmentioning
confidence: 99%